Conceptualization of economic security in the context of energy markets' integration - Uliana Bihun (CES Working Papers, 2018)
The research includes an analysis of the evolution of fundamental scientific theories regarding security. Based on the systematization of modern definitions the author suggests applying the institutional-transformational approach in order to comprehension the term “economic security of energy market”. The author emphasizes the influence of the theory of risk, the theory of conflict and theory of socio-economic catastrophes on the economic security of energy market. The author studies global trends in the development of the energy sector and determines the positions of Ukraine based on the indicators of the rating “Energy Trilemma Index” In the paper, the conceptual principles of economic security of energy markets, which these take into account peculiarities of integration processes, “acquis communautaire”, and stakeholders' interests, are presented. It gives the possibility to consider both economic and social-political factors of the market environment when establishing market priorities of every hierarchical level in a purpose of sustainable development achievement.
Keywords: 330; theories of security; integration; energy market; economic security